2018
DOI: 10.2478/aucft-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stachyose on Synbiotic Yogurt Obtained from Goat Milk with Lactobacillus acidophilus and Lactobacillus casei

Abstract: Development of synbiotic yogurt having multiple health benefits has become a new trend. The purpose of this study was to obtain the optimum stachyose concentration of the goat yogurt fermented by probiotics including Lactobacillus acidophilus (LA) or Lactobacillus casei (LC) besides Streptococcus thermophilus and Lactobacillus bulgaricus by measuring pH, acidity, viable counts and the change of stachyose content. The optimal stachyose concentration of goat LA-yogurt and goat LC-yogurt were 0.4% and 0.8%. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…According to Gopal (2011), the growth of L. acidophilus in yogurt is favored by the presence of metabolites such as formic acid and possibly by carbon dioxide and pyruvate, both produced by the colonies of S. thermophilus present in the medium. Similar results were found by Shu et al (2018) in a study with goat milk yogurt with the addition of Lactobacillus acidophilus. The authors obtained a pH reduction from 5.4 to 4.5 by varying the concentration of L. acidophilus from 6.48 to 7.18 log CFU/g in a 3-hour fermentation.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…According to Gopal (2011), the growth of L. acidophilus in yogurt is favored by the presence of metabolites such as formic acid and possibly by carbon dioxide and pyruvate, both produced by the colonies of S. thermophilus present in the medium. Similar results were found by Shu et al (2018) in a study with goat milk yogurt with the addition of Lactobacillus acidophilus. The authors obtained a pH reduction from 5.4 to 4.5 by varying the concentration of L. acidophilus from 6.48 to 7.18 log CFU/g in a 3-hour fermentation.…”
Section: Resultssupporting
confidence: 88%
“…Parvarei et al (2021) also observed a reduction in pH and an increase in acidity in yogurt samples with L. acidophilus during 28 days of storage at 4 ºC. Some research has investigated alternatives to increase the viability of L. acidophilus in goat milk yogurts, such as the addition of honey (Machado et al, 2017) and the incorporation of prebiotics, such as stachyose (Shu et al, 2018). These ingredients are favorable to the growth of the probiotic strain, increasing the functional character of fermented milk products.…”
Section: Resultsmentioning
confidence: 99%